Analisis Akreditasi, Kebutuhan Pelatihan Pegawai, Ketersediaan Anggaran Pelatihan Pegawai dan Serapan Anggaran Pelatihan Pegawai Tahun 2022 di Rumah Sakit Umum Daerah (RSUD) Kota Malang - Nurfadila, Lailatul; Mahsuni, Abdul Wahid; Junaidi, Junaidi (Universitas Islam Malang, 2023)
This study employs a descriptive qualitative methodology, a type of inquiry used to assess the state of natural things. Where the researcher has the key to the device. Triangulation or combination procedures are used in data collecting techniques. Data gathered through documentation and interviews. Data display, reduction, inference, or verification methods are used in data analysis. where the goal is to comprehensively analyze the primary research topics, which include accreditation, employee training requirements, availability of employee budgets, and staff training budget use in Malang City Hospital. Malang City Hospital has conducted an analysis of employee training, employee accreditation, personality of the training budget, and absorption of employee training in compliance with applicable rules. However, because the hospital's strategic plan has not been reviewed, there is uncertainty over the required training and the available funding.Keywords : Accreditation, employee training requirements, availability of employee budgets, and absorption of employee training.